Where Is the Civic Responsibility in Service Learning? A Process-oriented Empirical Study - Karl-Heinz Gerholz; Julia Holzner; Andreas Rausch (Forum Neue Medien in der Lehre Austria, 2018)
It is essential to have engaged citizens for a functioning democracy. Consequently, educational processes must foster the active engagement of citizens. This could be enabled by the concept of service learning. Empirical studies on the effects of service learning on civic responsibility are ambiguous, however, a positive trend can be described. Retrospective self-disclosure of students, which is normally used in empirical studies, is impaired by memory effects. For this reason, this study is process-oriented with a weekly reflection in the form of a journal. The claim of the study is to explore key situations in the service learning module, which stimulate the students to think about civic engagement in society. The results show that key situations occur in interacting processes between the partner of the charitable organizations and the fellow students, as well as during the scientific work on the service project. Therefore, the interaction among students also seems relevant for triggering the consideration of civic engagement. This indicates that regarding service learning courses, students can be stimulated to find their own role in a society and position concerning civic engagement, but less so to foster a willingness to be engaged.